Entrepreneurship for the Creative and Cultural Industries - Kolb, Bonita M. (Milton : Routledge, 2020)
Artists, musicians, actors, singers, designers and other creative individuals need to understand basic business concepts if they are to successfully pursue their chosen artistic profession. These skills have historically not been taught to creative students, which leaves them unprepared to make a living from their artistic efforts. Entrepreneurship for the Creative and Cultural Industries will teach the basics of business in a way that is relevant to the challenges of running a small business marketing a creative product. Whether it is understanding the basics of business language, appreciating the crucial importance of finance, or using social media marketing, this innovative textbook covers the entrepreneurial skills required to succeed in the creative sector. Including advice from artists who have turned their idea into a profitable business and worksheets that can be combined into a simple business plan, Kolb helps non-business-minded creatives to understand everything they need to succeed in the increasingly competitive creative economy. This textbook is essential reading for non-business students who are looking to understand the business side of the creative sector, while its practical style will also suit recent graduates in these industries.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: ART / Business Aspects; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship; Artists; Entrepreneurship; Arts -- Marketing; Arts -- Economic aspects; Cultural industries -- Management